Person-Centered Therapy-Based Counseling Services: A Literature Review and Practical Implications - Kuswati, Lilik; Purwoko, Budi; All Habsy , Bakhrudin (Jurnal Indonesia Sosial Sains, 2026)
Guidance and counseling services require a strong theoretical foundation to build effective therapeutic relationships. Person-Centered Therapy (PCT), developed by Carl Rogers, offers a humanistic approach that places the client as the primary agent in the process of change. This article aims to comprehensively map the concepts, mechanisms, and practical implications of PCT in the context of counseling services through a literature review method. This writing uses a narrative literature study design with data sources derived from national (SINTA, Garuda) and international (PubMed/StatPearls) journal databases. The results of the study show that the success of PCT is highly dependent on the creation of core conditions by counselors, namely empathy, unconditional positive regard, and congruence. The thematic findings highlight the role of PCT in improving self-concept, increasing resilience in vulnerable populations, and facilitating self-actualization through an equal partnership relationship between counselors and counselors. The practical implications of this study underscore the importance of active listening and reflection skills training for guidance and counseling practitioners to improve the quality of services in various educational and community settings. In conclusion, PCT remains relevant as the foundation of assistance relations that humanize humans in the modern era. Watson et al. (2011) affirm that empathic attunement within a person-centred frame is a transtheoretically validated mechanism of change that underpins therapeutic effectiveness regardless of specific orientation